Dampak Penggunaan Gadget terhadap Keharmonisan Keluarga Kristiani di Stasi Santo Petrus dan Paulus Hilimaenamolo Telukdalam - Evimawati Harefa; Sergius Lay; Elisabeth Firdalis Zagoto (Journal New Light, 2025)
This research was motivated by the increase in gadget use that occurred during the corona virus (covid-19) pandemic which had a negative impact on children and parents. Where children and adults are less able to control themselves when using gadgets. The variable in the research is the impact of gadget use on family harmony. The aim of this research was carried out by researchers to determine the impact of gadget use on Christian family harmony. The research method used is qualitative research with a case study approach. The sample selection in this research used a purposive sampling technique. Data collection techniques were carried out using observation, interviews and documentation techniques. Data validity testing was carried out using triangulation, namely data source triangulation and technical triangulation. Based on research that has been carried out, it was found that the use of gadgets has a negative impact on family harmony. Where, gadget users cannot control themselves in using gadgets beyond their needs. So gadget users become selfish individuals, busy with their own world, whether playing games, playing tik-tok, and watching videos without time limits. This results in less communication within the family.